Impact of Digitalization Business Communication and Pricing on Consumer Satisfaction and Customer Loyalty - Nurmatriani, Erika; Sidik, Muh (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The digital business landscape in Indonesia is witnessing significant growth. This is evident from the increasing number of e-commerce platforms emerging in the market. Notably, several of these platforms have experienced rapid expansion, achieving unicorn status. This economic digitalization presents unique opportunities for the micro, small, and medium enterprises (MSMEs) sector. Micro, small, and medium enterprises (MSMEs) in Purwakarta Regency, West Java, have expressed concerns regarding the digitalization progress, which has not yet fully supported the existence of MSMEs and competition in trade with Chinese products, which are significantly cheaper in the e-commerce sector. Effective business communication training is essential for product promotion in the digital marketplace, as well as for developing competitive pricing strategies for micro, small, and medium enterprises (MSMEs) with the ultimate goal of enhancing consumer satisfaction and loyalty towards products from MSMEs in Purwakarta. This study aims to investigate the extent to which business communication strategies and pricing strategies can improve consumer satisfaction and loyalty towards MSME products in Purwakarta, West Java. The research employs a descriptive quantitative approach with a sample size of 104 online shoppers via Instagram. The findings indicate a significant positive indirect effect of business communication on customer loyalty through consumer satisfaction as an intervening variable, as well as a significant positive indirect effect of pricing on customer loyalty through consumer satisfaction as an intervening variable. However, there are limitations, particularly regarding the in-depth exploration of the weaker dimensions of the pricing strategy variable, which could be addressed in future research.